Caracterização de um modelo experimental de ansiedade humana baseado na exibição de filmes - Barbosa, Vânia dos Santos (2014)
Objective: In the study of anxiety, the bridge between preclinical research and clinical trials with patients is represented by models of experimental anxiety in humans, which induce anxiety in healthy volunteers in a controlled manner. The present study aimed to investigate an experimental model of human anxiety, based on of the presentation of an anxiogenicscene either isolated (clip) or as part of a full-length movie(plot). Method: Thirty healthy male volunteers were allocated to two groups: Clip (n = 15) and Plot (n = 15). Psychological (through a standardized scale, namely, the State-Trait Inventory Anxiety, and numerical scales /analog)and physiological (through the records of changes in heart rate, temperature change endpoints, skin conductance and muscle tension) parameters were evaluated while subjects watched a white screen (baseline), a neutral scene and an anxiogenic scene. Results: The data a physiological stress response during the anxiogenic scene for both groups. However, the subjective anxiety response was less intense in the Clip group, and it could only be detected by the State-Trait Anxiety Inventory, which is a more elaborate anxiety measuring instrument than the commonly used analog/numeric scales. Conclusion: The data support the employment of movies that involve situations of danger as a method of inducing experimental anxiety.